Clitopilus cretoalbus sp. nov. (Entolomataceae, Agaricales), a new species from Pakistan - Izhar, Aiman; Khan, Zaman; Asif, Muhammad; Bashir, Hira; Rani, Afifa Kainat; Niazi, Abdul Rehman; Khalid, Abdul Nasir (European Journal of Taxonomy, 2023)
A new species, Clitopilus cretoalbus A.Izhar, Zaman, M.Asif, H.Bashir, Niazi & Khalid sp. nov., is described herein based on several collections from Punjab, Pakistan. It is characterized by a clitocyboid to somewhat omphaloid stature combined with a white pileus, decurrent lamellae, an almost central to slightly eccentric whitish relatively long stipe, the occurrence of cheilocystidia, and basidiospores with 6 to 9 ridges in polar view. Molecular phylogenetic analyses of nrITS and nrLSU performed using the maximum likelihood method supported the novelty of this Pakistani species and its placement within the genus Clitopilus section Scyphoides. A comparison with other morpho-anatomically close species confirmed that the newly described species is distinct from others.